Algae and Their Metabolites as Potential Bio-Pesticides - Asimakis, Elias; Shehata, Awad A.; Eisenreich, Wolfgang; Acheuk, Fatma; Yılmaz, Mete (MDPI, 2022)
An increasing human population necessitates more food production, yet current techniques in agriculture, such as chemical pesticide use, have negative impacts on the ecosystems and strong public opposition. Alternatives to synthetic pesticides should be safe for humans, the environment, and be sustainable. Extremely diverse ecological niches and millions of years of competition have shaped the genomes of algae to produce a myriad of substances that may serve humans in various biotechnological areas. Among the thousands of described algal species, only a small number have been investigated for valuable metabolites, yet these revealed the potential of algal metabolites as bio-pesticides. This review focuses on macroalgae and microalgae (including cyanobacteria) and their extracts or purified compounds, that have proven to be effective antibacterial, antiviral, antifungal, nematocides, insecticides, herbicides, and plant growth stimulants. Moreover, the mechanisms of action of the majority of these metabolites against plant pests are thoroughly discussed. The available information demonstrated herbicidal activities via inhibition of photosynthesis, antimicrobial activities via induction of plant defense responses, inhibition of quorum sensing and blocking virus entry, and insecticidal activities via neurotoxicity. The discovery of antimetabolites also seems to hold great potential as one recent example showed antimicrobial and herbicidal properties. Algae, especially microalgae, represent a vast untapped resource for discovering novel and safe biopesticide compounds.
Keywords: cyanobacteria; algal extracts; antimicrobial; plant defense; photosynthesis